An overview of how on‐call consultant paediatricians can recognise and manage severe primary immunodeficiencies. (23rd August 2019) - Wekell, Per; Hertting, Olof; Holmgren, Daniel; Fasth, Anders
Abstract: Severe primary paediatric immunodeficiency syndromes are rare and potentially fatal unless suspected, diagnosed and treated early. We provide clinical guidance and support for on‐call consultant paediatricians working in secondary level hospitals on how to recognise and manage children with these conditions. Our paper addresses four conditions that risk the most severe outcomes if they are not adequately cared for during on‐call periods, such as weekends: severe combined immunodeficiency, haemophagocytic lymphohistiocytosis, severe congenital neutropaenia and chronic granulomatous disease. Conclusion: On‐call paediatricians are provided with advice on handling the most severe primary immunodeficiencies. Abstract :